Mechanism Optimization Design of Multi-bar Light-load Stamping Press - Yang Xu; Yuanchao Deng; Zhiqiang Xu (Jixie chuandong)
In order to give full play to the mechanical properties of stamping machine，a multi-bar mechanism is used to replace a manual production to solve a series of problems when stamping sponge blank. A mechanism model is constructed and a kinematic analysis is carried out； A mathematical model for optimizing the geometric parameters of multi-bar light-load stamping machine is established，which takes the maximum effective stamping angle of crank and the minimum fluctuation of acceleration of main slider in the effective stamping stroke as evaluation criteria； The optimization model of the mechanism is constructed by step search method with Matlab，and then a simulation analysis is carried out with Adams. The optimization results show that within the range of effective stamping stroke，the effective stamping time increases by 22.03% and the effective stamping angle increases by 25.43%. The increase of effective stamping time and effective stamping angle can prolong the deformation time of the workpiece，which is beneficial to the full deformation of the workpiece and improve the machining quality of the blank. The fluctuation of acceleration of the main slider in the effective stamping stroke is reduced by 10.63%，which means that the inertia force of the whole mechanism is reduced and the stamping accuracy is increased to a certain extent.